Comparing Defensive Mechanisms and Suicidal Thoughts in Addicted Men and Women - Sadeghi Nia, Kimia; Asmaee Majd, Sirvan (Health Nexus, 2023)
The present study aimed to compare the defensive mechanisms and suicidal thoughts among substance-dependent men and women. The research design was a retrospective (causal-comparative) study. The sample included 112 substance users (56 women and 56 men) from addiction rehabilitation centers in Gilan province, selected through convenience sampling based on entry criteria for this study. Two questionnaires were used in this study: the Defense Style Questionnaire (DSQ-40) and the Beck Scale for Suicide Ideation (BSSI). The collected data were analyzed using multivariate analysis of variance with SPSS software version 26. Data analysis showed no significant difference in the defensive mechanisms between men and women dependent on substances; however, there was a significant difference in suicidal thoughts between men and women dependent on substances. Considering the results of this study, therapists and counselors working with substance-dependent individuals are advised to pay attention to the defensive mechanisms and suicidal thoughts of these individuals, as awareness of these variables can assist in providing better and more appropriate services to these patients.